Phenetic analysis and habitat preferences of wild orchids in Gunung Gajah, Purworejo, Indonesia - Theresia Henny Primasiwi Purba; Abdul Razaq Chasani (Society for Indonesian Biodiversity, 2021)
Abstract. Purba THP, Chasani AR. 2021. Phenetic analysis and habitat preferences of wild orchids in Gunung Gajah Purworejo. Biodiversitas 22: 1371-1377. Orchid (Orchidaceae) is one of the largest flowering plant families comprising more than 25.000 species. Knowledge of wild orchid diversity and their habitat preferences is useful for its conservation efforts. Research of wild orchid diversity in Indonesia has been done before, however, there is still few information about phenetic analysis and habitat preferences of wild orchids in Indonesia particularly in Gunung Gajah, Purworejo, Indonesia. Therefore, our research aimed to study species diversity and phenetic relationship of wild orchids and their habitat preferences in Gunung Gajah, Purworejo. Exploration was done using purposive sampling method. Phenetic analysis was carried out using MVSP 3.1, implemented by clustering method to understand phenetic relationships and ordination by PCA method to reveal morpho-anatomical characters which determine the clustering pattern. Thirteen orchid species of subfamily Vanilloideae, Orchidoideae, and Epidendroideae were found. Two clusters were formed on dendrogram and each of them was separated into two sub-clusters. PCA analysis based on stem, leaf, and flower characters showed different clusters compared to dendrogram. Habitat preferences of wild orchids in Gunung Gajah are alkaline soil, low soil moisture, air temperature 24-29°C, and low to high light intensity. Epiphytic orchids preferences on their host tree are dominated by median and upper part of main stem.